Nanocable-structured polymer/carbon nanotube composite with low dielectric loss and high impedance. (July 2017) - Ren, Junwen; Yu, Demei; Feng, Lihua; Wang, Guolong; Lv, Guowei
Abstract: A hierarchical nanocable structure was fulfilled by grafting poly(glycidyl methacrylate) from single walled carbon nanotubes (PGMA-SWCNTs) via activators regenerated by electron transfer-atom transfer radical polymerization (ARGET-ATRP). It was found that SWCNTs were parallelly separated by the grafted PGMA brushes in the nanocables. To investigate the advantages of nanocable architecture, a composite film was prepared through filtrating the uniform solution of PGMA-SWCNTs nanocables. The dielectric properties dependent on frequency and temperature revealed that high dielectric constants, high impedance and low dielectric loss were simultaneously achieved for the PGMA-SWCNTs film. Meanwhile, thermal conductive analysis showed that the PGMA-SWCNTs film possessed a high thermal conductivity. The unique nanocable structure and the excellent interfacial interaction between PGMA and SWCNTs were believed to be the critical causes for the high performance of the nanocomposite.